2003
DOI: 10.1046/j.1398-9995.2003.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological effects of low‐dose IFN‐α treatment in patients with corticosteroid‐resistant asthma

Abstract: Interferon-alpha treatment was associated with dramatic improvements in the condition of patients with corticosteroid-resistant asthma with and without Churg-Strauss syndrome. Potential mechanisms of action include the establishment of a correct Th1/Th2 balance and the induction of the anti-inflammatory IL-10 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 32 publications
3
73
0
4
Order By: Relevance
“…Interestingly, despite concerns about side effects, IFN-␣ treatment has been shown to be a successful option in the treatment of steroid-resistant asthma, and its mechanisms of actions are thought to involve the promotion of a Th1, rather than a Th2, immune response, thus disrupting the cycle of eosinophilic inflammation and airway hyperreactivity (24,25). Furthermore, it was shown that histamine, released during allergic inflammation, inhibits the secretion of IFN-␣ from plasmacytoid dendritic cells, which could promote a strong Th2 response, as in allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, despite concerns about side effects, IFN-␣ treatment has been shown to be a successful option in the treatment of steroid-resistant asthma, and its mechanisms of actions are thought to involve the promotion of a Th1, rather than a Th2, immune response, thus disrupting the cycle of eosinophilic inflammation and airway hyperreactivity (24,25). Furthermore, it was shown that histamine, released during allergic inflammation, inhibits the secretion of IFN-␣ from plasmacytoid dendritic cells, which could promote a strong Th2 response, as in allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…By taking advantage of its regulatory influence on the induction of Th1 responses (21)(22)(23), IFN-␣ has recently been used successfully in the treatment of steroid-resistant asthma and related diseases where an exaggerated Th2 immune response leads to eosinophilic lung disease (24,25).…”
mentioning
confidence: 99%
“…The molecular mechanism for these defects in innate immunity is not yet understood. Low-dose IFN-α seems to give marked benefit in patients with severe corticosteroid-resistant asthma but again the mechanism is unknown (30).…”
Section: Figurementioning
confidence: 99%
“…Regardless, our study identifies a new family of candidate genes for asthma/atopy association studies, for studies of the relationship between viral infections and the development or exacerbation of asthma, 49,50 and for pharmacogenetic studies of the differential response to IFN-a therapy in corticosteroid-resistant asthma and other atopic diseases. [27][28][29][30] …”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, reduced levels of IFN-a in patients with the Th2-associated diseases asthma and atopy have been reported, 25,26 and treatment with IFN-a therapy improves clinical symptoms in some patients. [27][28][29][30] Thus, we hypothesized that variation in one or more of these genes could modulate expression levels or function of the type I interferons and, as a result, influence the development or course of asthma and atopic diseases.…”
Section: Introductionmentioning
confidence: 99%